A Historical Survey of the Israeli Oppressions in Palestine: An Islamic Panacea - Abubakar, Ismail Hashim (KWASU Journal of Religious Studies, 2018)
The creation of the Zionist State of Israel has posed a series of cases of man's inhumanity to man in a mission to architect a Great Jewish Land that will encompass the majority of Arab Countries in the Middle-East. People in Palestine have, since 1948 and even before, forgotten peaceful days and serene nights. A discerning audience of this more-than-six- decade oppressions may discover that the Israeli occupation of Palestine and its merciless torture of the Palestinians are not limited to the Arab Muslims only. Palestinian Christians also suffer a great deal from the heartless treatment of the Zionist forces operating in that robbed land that is hitherto held in high esteem in a region regarded as the earliest human settlement. Ironically, many Christians especially in Nigeria seem to be oblivious of this fact, hence register their support to Israel and its cruelty. This paper attempts to survey around some of the instances of inhuman subjugations of the Israel against the Palestinians with a view to making a case that Christians also are not spared. It also proposes an Islamic panacea which, if followed accordingly, will bring the Jewish oppressions in Palestine to a halt. The paper relies on the library method of research whereby books as well as magazines were used. Its main findings reveal that to the possible surprise of many Nigerian Christians, Arab Christians in Palestine are not exempted in any inhuman scheme of Israeli's violence against the Palestinians. It concludes that unless Islamic therapy is employed and applied appropriately, Palestine will remain a victim of Israeli oppressions